อัตราชุกและปัจจัยที่เกี่ยวข้องกับการเกิดกลุ่มอาการป่วยเหตุอาคารของเจ้าหน้าที่ ที่ปฏิบัติงานภายในอาคารของโรงพยาบาลที่มีการระบายอากาศไม่เพียงพอ - ณัฐพงศ์ แหละหมัน (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This cross-sectional analytic study aimed at examining the prevalence rate related factors of sick building syndrome (SBS) among health care workers in hospital building. By using carbon dioxide level to be the indicator of ventilation condition, the study population were all health care workers in hospital with inadequate ventilation (carbon dioxide level in the building was more than 800 ppm.) and the comparison groups were health care workers in hospitals with adequate ventilation (Carbon dioxide level in the building was lower than 700 ppm.). The data were collected by questionnaires and the air samples (carbon dioxide, carbon monoxide, humidity, temperature, volatile organic compounds, particulate, matter, fungi, bacteria, nitrogen dioxide and ozone) were collected by industrial hygiene instruments from nine govermment hospitals in central region. Totally 1,800 questionnaires were distributed and 1,500 were returned, with the response rate of 83.3%. The results showed no significant difference the SBS prevalence rate between the study and the comparison groups (the prevalence rate of the study (95%CI) was 25.82 (22.92-28.71) versus 26.31 (22.64-29.97). The most frequency symptoms were eye (prevalence rate (95% CI) = 17.94 (15.42-20.45). Multivariable analysis showed that factors which were significantly associated with SBS were the total amount of dust in the building more than 0.1 mg/qb.m. (OR (95%CI) = 1.62 (1.24-2.11) working day per week more than 5 day (OR (95%CI) = 1.48 (1.14-1.93)), using printer (OR (95%CI) = 1.54 (1.18-2.01)), complaint about bad ventilation (OR (95% CI) = 1.46 (1.13-1.87)), dirty (OR (95%CI) = 2.09 (1.55-2.81)), noise (OR (95%CI) = 1.34 (1.01-1.79)). In conclusion, the study did not reveal the association between the inadequate ventilation and SBS in the hoapitals in central Thailand. However, the SBS prevalence rate of 25-26 percent almost reaches the problematic level of 30% which was proposed by the WHO. Attention shuld therefore be paid to minimize this problem beforehand.